2020
DOI: 10.1371/journal.pone.0243055
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and risk factors of disease in Nepal: Trend and projections from 1990 to 2040

Abstract: Background Between 1990 and 2017, Nepal experienced a shift in the burden of disease from communicable, maternal, neonatal and nutritional (CMNN) diseases to non-communicable diseases (NCDs). With an increasing ageing population and life-style changes including tobacco use, harmful alcohol consumption, unhealthy diets, and insufficient physical activity, the proportion of total deaths from NCDs will continue to increase. An analysis of current diseases pattern and projections of the trends informs planning of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…A study by Pandi et al In Nepal predicted the prevalence of hypertension using the simulation method by 2040. The results showed that the prevalence of hypertension in this country will also be upward [ 33 ]. Another study, which examined the prevalence of hypertension in urban areas by 2030 with an analysis of 32 studies, predicted that the prevalence of hypertension would be upward and to 32% in women, 36.5% in men and 34.5% in general [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study by Pandi et al In Nepal predicted the prevalence of hypertension using the simulation method by 2040. The results showed that the prevalence of hypertension in this country will also be upward [ 33 ]. Another study, which examined the prevalence of hypertension in urban areas by 2030 with an analysis of 32 studies, predicted that the prevalence of hypertension would be upward and to 32% in women, 36.5% in men and 34.5% in general [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A body mass index above 22.5 can lead to cardiovascular disease and high blood pressure. A study by Pandi et al In Nepal predicted the prevalence of obesity using the simulation method, which shows the prevalence of obesity up to 2040 with a steep slope [ 33 ]. Findings from a study in the United States show that by 2030, approximately one in two adults will be obese, with a prevalence of more than 50 percent in 29 states and no less than 35 percent in any state [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“… 3 Mortality due to diabetes in Nepal is projected to increase from 8.68% in 2015 to 15.52% in 2040. 4 …”
Section: Introductionmentioning
confidence: 99%
“…The epidemiological transition has seen an increase in non-communicable diseases in Nepal, which represented nearly two-thirds of total deaths in 2015, compared to less than 30% in 1990 [10]. This mortality, particularly due to diabetes and cardiovascular diseases, is projected to rise alongside socioeconomic development [11].…”
Section: Introductionmentioning
confidence: 99%